Magnesium enhances aurintricarboxylic acid’s inhibitory action on the plasma membrane Ca2+-ATPase - Souto Guevara, Cecilia Alfonsina (2024)
Our research aimed to elucidate the mechanism by which aurintricarboxylic acid (ATA) inhibits plasma membrane Ca2+-ATPase (PMCA), a crucial enzyme responsible for calcium transport. Given the pivotal role of PMCA in cellular calcium homeostasis, understanding how it is inhibited by ATA holds significant implications for potentially regulating physiopathological cellular processes in which this pump is involved. Our experimental findings revealed that ATA employs multiple modes of action to inhibit PMCA activity, which are influenced by ATP but also by the presence of calcium and magnesium ions. Specifically, magnesium appears to enhance this inhibitory effect. Our experimental and in-silico results suggest that, unlike those reported in other proteins, ATA complexed with magnesium (ATA•Mg) is the molecule that inhibits PMCA. In summary, our study presents a novel perspective and establishes a solid foundation for future research efforts aimed at the development of new pharmacological molecules both for PMCA and other proteins.